Political developments in the state of Yemen and attempts to restore the Ottoman authority 1840-1849 AD (Journal of the College of Basic Education, 2023)
Summary of the research:After the end of the Egyptian presence in Yemen in 1840, which was preceded by the British occupation of Aden in 1839, the state of Yemen afflicted a lot of chaos and turmoil and the loss of unified authority. Therefore, during the period 1840-1849 we will notice vigorous attempts to restore Ottoman authority over the state of Yemen, whether by relying on local personalities such as Ashraf Hijaz, the supervision of Abu Arish, the imams of Sana’a, and the sending of government delegates, but these means led to an exacerbation of chaos and an increase in external dangers, especially the British threat in Aden, so the best option to restore the state was the military option, so the campaign of 1849 was to Yemen, but it also did not succeed in approving the affairs of the state.Keywords: the mandate of Yemen, the London Treaty of 1840, the Yemen campaign of 1849, Sharif Hussein, the ruler of Abu Arish, Sharif Muhammad bin Aoun